Tanggung Jawab Pemuda terhadap Masa Depan Pancasila - Despan Heryansyah (Fakultas Hukum Universitas Islam Indonesia, 2014)
Pancasila has not provided a great influence on the development of Indonesia. This is caused by the history of the implementation of Pancasila which is laden with irregularities committed by the authorities. The problem in this study is, first, how is the responsibility of the youth to the future of Pancasila? Second, what are the values contained in Pancasila. This research is doctrinal. Legal materials used in the form of primary and secondary legal materials. The method used the philosophical approach and historical approach. The finding of this study concluded that, first, youth personal responsibility is to continue the improvement of the character by studying and implementing the values of Pancasila. Secondly, Pancasila containing the noble values of divinity, humanity, unity, democracy, and justice must be instilled as early as possible within Indonesian society.